2014
DOI: 10.1111/1365-2656.12272
|View full text |Cite
|
Sign up to set email alerts
|

How topography induces reproductive asynchrony and alters gypsy moth invasion dynamics

Abstract: Summary 1.Reproductive asynchrony, a temporal mismatch in reproductive maturation between an individual and potential mates, may contribute to mate-finding failure and Allee effects that influence the establishment and spread of invasive species. Variation in elevation is likely to promote variability in maturation times for species with temperature-dependent development, but it is not known how strongly this influences reproductive asynchrony or the population growth of invasive species. 2. We examined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…Consistent with many studies (Keitt et al , Wang and Kot , Wang et al ), increasing the Allee parameter slowed the mean rate of spread. These and other studies, however, represented Allee effects using a constant value and our findings, motivated by growing recognition of spatiotemporal variability in Allee effects (Tobin et al , Kramer and Drake , Kramer et al , Walter et al ), add nuance to predictions of range expansion in heterogeneous landscapes. We found that spatial variations in Allee effects, and the structure of the variation, can drive deviations from predictions generated assuming a spatially constant Allee effect (Table , Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with many studies (Keitt et al , Wang and Kot , Wang et al ), increasing the Allee parameter slowed the mean rate of spread. These and other studies, however, represented Allee effects using a constant value and our findings, motivated by growing recognition of spatiotemporal variability in Allee effects (Tobin et al , Kramer and Drake , Kramer et al , Walter et al ), add nuance to predictions of range expansion in heterogeneous landscapes. We found that spatial variations in Allee effects, and the structure of the variation, can drive deviations from predictions generated assuming a spatially constant Allee effect (Table , Fig.…”
Section: Discussionmentioning
confidence: 63%
“…climate), and also vary in response to habitat patchiness. Gradients in Allee effects could result if, for example, there are elevational or latitudinal gradients in mating success (Rhainds and Fagan , Lynch et al , Walter et al ), predation pressure (McKinnon et al ), or other biotic interactions (Schemske et al ). Other types of landscape heterogeneity, such as variation in habitat type, often display patchiness, and the spatial scale of habitat patchiness – relative to the scale of dispersal – may impact habitat occupancy (Hanski et al ) and rates of movement (With and Crist ) of a focal species as well as its natural enemies (Yahner and Smith , Cronin and Reeve ).…”
mentioning
confidence: 99%
“…, Walter et al. ). In its original form, the model was used to assess how mate finding and Allee effects were affected by reproductive asynchrony, i.e., mismatches in the timing of reproductive activity among potential mates.…”
Section: Methodsmentioning
confidence: 99%
“…, Walter et al. ). In addition, long‐term spatially explicit data on gypsy moth abundance over large areas permit uniquely detailed analysis of spread in real landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Spread rates in this region were found to be negatively correlated to hours of spring/summer temperature above optimal for gypsy moth growth (Tobin et al., ). Elevational gradients may also play a role by creating phenological differences between adjacent populations, which can affect spread rates (Walter, Meixler, et al., ). Research that partitioned potential anthropogenic factors found that personal firewood use had the strongest relationship to gypsy moth spread rates (Bigsby, Tobin, & Sills, ).…”
Section: Contributions To Understanding Spatial Spreadmentioning
confidence: 99%